Traditional games for physical fitness in primary school students: A systematic review in Indonesia - Zulnadila, Zulnadila; Suharjana, Suharjana; Arjuna, Fatkurahman; Sriwahyuniati, Christina Fajar; Mappanyukki, Andi Atssam; Rahman, Abdul; Agustina, Dina; Szczepocki, Matthew (Tanjungpura Journal of Coaching Research, 2025)
Background and Study Aim. Physical fitness is a very important factor for students to fight fatigue when doing activities, so that during the learning process at school students can still concentrate on learning. Information on physical fitness in elementary school students is a source of health that really needs to be considered. Therefore, this study aimed to review the scientific literature on physical fitness of primary school children through learning with traditional games in Indonesia.Material and Methods. The search in this study used databases such as ScienceDirect, Scopus, Google Scholar, and PubMed. The search began using the ScienceDirect database, then Scopus, Google Scholar and PubMed. The search strategy included a combination of keyword variations ("traditional games" OR "Play Model" AND "physical fitness" AND "students" AND "elementary school"). The search was conducted following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. After following the exclusion criteria, only 6 articles remained.Results. The results showed that the provision of traditional games can improve students' physical fitness. Traditional games are developed with a play approach and activities are designed according to the basic movement skills possessed or are in their developmental stage. Traditional games have values and elements of movement that are in accordance with the need to develop basic skills.Conclusions. This increase occurs because of traditional games that can encourage children to be actively involved in learning, want to do movements and effectively improve physical fitness. That way, in the context of physical learning conceptualized in a traditional game can be applied.